Rio Tinto, impacto do declínio econômico na organização Espacial - Dantas, Anna Aline Roque Santana (2009)
This work presents the process of physical transformation occurred on the urban structure of the city of Rio Tinto, a marked example of Brazilian work village located on the Northern cost of the state of Paraíba. That transformation has been a result of the closing of an important city textile industry in 1983 and has been occurring from that date until the present time (2009). It is also analyzed how the new social, economic and governmental relationships have promoted changes on the landscape physiognomy and on the definition of new urban structure. It was necessary a review of theoretical and historiographical references, including since the arising of the working class and its situation in Europe till its connection with Brazilian industrialization history. The dissertation examines separately three main components of urban process transformation: changes in use and occupation of urban land, changes in architectural buildings and new implantations of urban structures and buildings.